THEORETICAL APPROACHES IN THE FORMATION OF REFLECTIVE COMPETENCE (TAMADDUN NURI JURNALI, 2024)
This article focuses on the methods of developing reflexive competence of students in foreign language teaching, which help to increase the student's intellectual competence on the basis of tasks that motivate students, cooperation technology. Also, the official and scientific literature on the topic of this article is summarized and general conclusions are given on the existing discussions.